<< Chapter < Page Chapter >> Page >

Performing algebraic operations on functions

Find and simplify the functions ( g f ) ( x ) and ( g f ) ( x ) , given f ( x ) = x 1 and g ( x ) = x 2 1. Are they the same function?

Begin by writing the general form, and then substitute the given functions.

( g f ) ( x ) = g ( x ) f ( x ) ( g f ) ( x ) = x 2 1 ( x 1 ) = x 2 x = x ( x 1 )   ( g f ) ( x ) = g ( x ) f ( x ) ( g f ) ( x ) = x 2 1 x 1 = ( x + 1 ) ( x 1 ) x 1 where  x 1 = x + 1

No, the functions are not the same.

Note: For ( g f ) ( x ) , the condition x 1 is necessary because when x = 1 , the denominator is equal to 0, which makes the function undefined.

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Find and simplify the functions ( f g ) ( x ) and ( f g ) ( x ) .

f ( x ) = x 1     and     g ( x ) = x 2 1

Are they the same function?

( f g ) ( x ) = f ( x ) g ( x ) = ( x 1 ) ( x 2 1 ) = x 3 x 2 x + 1 ( f g ) ( x ) = f ( x ) g ( x ) = ( x 1 ) ( x 2 1 ) = x x 2

No, the functions are not the same.

Got questions? Get instant answers now!

Create a function by composition of functions

Performing algebraic operations on functions combines them into a new function, but we can also create functions by composing functions. When we wanted to compute a heating cost from a day of the year, we created a new function that takes a day as input and yields a cost as output. The process of combining functions so that the output of one function becomes the input of another is known as a composition of functions . The resulting function is known as a composite function . We represent this combination by the following notation:

( f g ) ( x ) = f ( g ( x ) )

We read the left-hand side as f composed with g at x ,” and the right-hand side as f of g of x . The two sides of the equation have the same mathematical meaning and are equal. The open circle symbol is called the composition operator. We use this operator mainly when we wish to emphasize the relationship between the functions themselves without referring to any particular input value. Composition is a binary operation that takes two functions and forms a new function, much as addition or multiplication takes two numbers and gives a new number. However, it is important not to confuse function composition with multiplication because, as we learned above, in most cases f ( g ( x ) ) f ( x ) g ( x ) .

It is also important to understand the order of operations in evaluating a composite function. We follow the usual convention with parentheses by starting with the innermost parentheses first, and then working to the outside. In the equation above, the function g takes the input x first and yields an output g ( x ) . Then the function f takes g ( x ) as an input and yields an output f ( g ( x ) ) .

Explanation of the composite function.

In general, f g and g f are different functions. In other words, in many cases f ( g ( x ) ) g ( f ( x ) ) for all x . We will also see that sometimes two functions can be composed only in one specific order.

For example, if f ( x ) = x 2 and g ( x ) = x + 2 , then

f ( g ( x ) ) = f ( x + 2 ) = ( x + 2 ) 2 = x 2 + 4 x + 4

but

g ( f ( x ) ) = g ( x 2 ) = x 2 + 2

These expressions are not equal for all values of x , so the two functions are not equal. It is irrelevant that the expressions happen to be equal for the single input value x = 1 2 .

Note that the range of the inside function (the first function to be evaluated) needs to be within the domain of the outside function. Less formally, the composition has to make sense in terms of inputs and outputs.

Questions & Answers

the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
tan hyperbolic inverse (x+iy)=alpha +i bita
Payal Reply
prove that cos(π/6-a)*cos(π/3+b)-sin(π/6-a)*sin(π/3+b)=sin(a-b)
Tejas Reply
why {2kπ} union {kπ}={kπ}?
Huy Reply
why is {2kπ} union {kπ}={kπ}? when k belong to integer
Huy
if 9 sin theta + 40 cos theta = 41,prove that:41 cos theta = 41
Trilochan Reply
what is complex numbers
Ayushi Reply
Please you teach
Dua
Yes
ahmed
Thank you
Dua
give me treganamentry question
Anshuman Reply
Solve 2cos x + 3sin x = 0.5
shobana Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask